Properties of single layer particleboard from oil palm trunk particles / Siti Zalifah Mahmud ...[et al.] - Mahmud, Siti Zalifah; Ahmad, Nurrohana; Kasim, Jamaludin; Musa, Maisarah; Ramli, Mohd Fauzi; Abdul Rahman, Norshuhadaniza (2009)
Single layer or homogeneous particleboard was produced using oil palm trunk particles. Oil palm trunk was supplied by MPOB, Bangi. The trunk bark was removed using a headrig and then cut into smaller blocks and flaked using a disc flaker to produce strand-like particles. These strands were then passed through a dust extractor to reduce them into particles. This study determined the mechanical and physical properties of single layer particleboard from unscreened OPT particles using 7%, 9% and 11% phenol formaldehyde (PF) resin. The target board densities were 500 kg/m3 , 600 kg/m3 and 700 kg/m3, respectively, with board thickness of 12 mm and 19 mm. From the results, it shows that the increasing resin contents and board densities increased the mechanical properties and improved the physical properties of the particleboard, respectively. Thicker boards increased the mechanical properties of MOR and MOE and improved the physical properties of the particleboard. Generally, the effects of resin content, board densities and board thickness greatly influenced the mechanical and physical properties of the particleboard made from oil palm trunk particles.